Millimeter-wave imaging concepts: Synthetic Aperture Radar (SAR) and Digital Beam Forming (DBF) - Gumbmann, Frank; Tran, Hue Phat; Cenanovic, Amir; Methfessel, Sebastian Dirk (Frequenz, 2009)
Short range radar imaging systems for various security and non-destructive testing (NDT) applications are mainly based on synthetic aperture radar (SAR) or digital beam forming (DBF) techniques. In this article the development of a real-time SAR and a real-time DBF system is presented. The goal is to achieve a 3D image of a large measurement area with a high lateral and range resolution in order to detect suspicious items or material approach. This can be realized with a SAR system which is based on a new rotating virtual antenna concept. Another approach is a digital beam forming concept consisting of spatially distributed transmitters and receivers. Experimental results on specific test objects are presented to prove the performance of both concepts.
UnivIS-Import:2015-03-09:Pub.2009.tech.IE.LEH.millim
Keywords: Digital beam forming; Millimeter-wave imaging; Synthetic aperture radar